2012
DOI: 10.26418/jpmipa.v1i2.197
|View full text |Cite
|
Sign up to set email alerts
|

Pendekatan Pembelajaran Konflik Kognitif Untuk Meningkatkan Penguasaan Konsep Siswa Sma Pada Topik Suhu Dan Kalor

Abstract: The goal of this research is to obtain the gain of student's conceptual understanding in applied cognitive conflict approach in heat and temperature. Method of the research is experiment that conducted at 10 th grade in one of senior high school in Bandung. Cognitive conflict approach was used on experiment group while control group used conventional approach. Data were collected through pretest, posttest, questionaire, and observation sheet. Data was analized statistically by t-test. The result showed that no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
1
5
0
4
Order By: Relevance
“…The results of this data analysis show that the application of cognitive conflict strategies can be used as an alternative to improve students' understanding of concepts. The results of this study are in line with the results of previous studies which found that the application of cognitive conflict strategies in physics learning was effective in increasing students' conceptual understanding (Sirait, 2010;Baser, 2016;Setyowari, et.al., 2011;Zuhdi & Makhrus, 2020).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results of this data analysis show that the application of cognitive conflict strategies can be used as an alternative to improve students' understanding of concepts. The results of this study are in line with the results of previous studies which found that the application of cognitive conflict strategies in physics learning was effective in increasing students' conceptual understanding (Sirait, 2010;Baser, 2016;Setyowari, et.al., 2011;Zuhdi & Makhrus, 2020).…”
Section: Resultssupporting
confidence: 91%
“…This cognitive conflict learning can also present concrete objects in learning a concept, namely through experimentation. Students are faced with real situations, namely through experiments, and are directly involved in the process of achieving the concept (Sirait, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fisika merupakan mata pelajaran yang berfungsi untuk memperluas wawasan pengetahuan tentang materi dan energi, meningkatkan keterampilan ilmiah, menumbuhkan sikap ilmiah, dan kesadaran/kepedulian pada produk teknologi melalui penerapan teori maupun prinsip fisika yang sudah dikuasai sebelumnya. Pernyataan tersebut sejalan dengan pendapat Sirait [3] yang mengatakan bahwa fisika merupakan salah satu cabang IPA yang pada dasarnya bertujuan untuk mempelajari dan menganalisis pemahaman kuantitatif gejala dan proses alam dan sifat zat beserta penerapannya.…”
Section: Pendahuluanunclassified
“…Setyowati, Subali & Mosik (2011) menyatakan bahwa konfklik ognitif dalam pembelajaran fisika pada materi tekanan mampu menumbuhkan kemampuan berpikir kritis, penguasaan konsep dan hasil belajar kognitif siswa. Selain itu penelitian Baser (2006) & Sirait (2012 menyatakan bahwa konflik kognitif dapat meningkatkan penguasaan konsep fisika siswa lebih signifikan dibandingkan dengan model konvensional. Hasil-hasil tersebut memperkuat hasil penelitian ini, yaitu adanya pengaruh strategi konflik kognitif dalam meningkatkan penguasaan konsep siswa.…”
Section: Gambar 1 Perbandingan Hasil Tes Awal Pengusaan Konsep Siswaunclassified